Nobiletin, a Citrus Flavonoid That Improves Memory Impairment, Rescues Bulbectomy-Induced Cholinergic Neurodegeneration in Mice - Akira Nakajima; Tohru Yamakuni; Mitsuya Haraguchi; Naoki Omae; Si-Young Song; Chieko Kato; Osamu Nakagawasai; Takeshi Tadano; Akihito Yokosuka; Yoshihiro Mimaki; Yutaka Sashida; Yasushi Ohizumi (Elsevier, 2007)
We have recently reported that nobiletin, a citrus flavonoid, improves impaired memory in olfactory-bulbectomized (OBX) mice, which have been widely utilized as a useful paradigm that shares some major clinical features of Alzheimer's disease. Here, we examined the effects of nobiletin on OBX-induced cholinergic neurodegeneration in mice. OBX mice showed reduced acetylcholinesterase (AChE) staining and choline acetyltransferase (ChAT) expression in the hippocampus. An 11-day administration of nobiletin rescued OBX-induced decrease in the density of AChE-staining and ChAT expression in the hippocampus. These results suggest that nobiletin rescues OBX-induced cholinergic neurodegeneration, accompanied by improvement of impaired memory in OBX mice. Keywords:: Alzheimer's disease, cholinergic neuron, nobiletin